Fenton-type bimetallic catalysts for degradation of dyes in aqueous solutions - Santos, Bebiana L. C. (2021)
Dye compounds are becoming a problematic class of pollutants for the environment, so it is important to develop stable catalysts for their elimination. First, several studies were performed with different Y zeolites (NaY, (NH4)Y and USY) in order to select the best support for the preparation of the bimetallic catalysts. In particular, NaY zeolite was used as the support for Fe, Cu and Mn metals to prepare mono and bimetallic Fenton-type catalysts by the ion exchange method. The catalysts were characterized by several techniques, such as chemical analysis, nitrogen physisorption, X-ray diffraction (XRD), scanning electron microscopy (SEM) and cyclic voltammetry studies. Characterization results revealed that the metals were successfully ion-exchanged within the NaY zeolite. The prepared catalysts were tested for the aqueous-phase degradation of dye compounds (Procion yellow (PY) and Tartrazine (Tar)) at atmospheric pressure and different temperatures, using H2O2 as the oxidant. All the investigated samples were found to be active in degrading the dyes through the Fenton-type process; however, the oxidation rate was found to be higher in the presence of the bimetallic catalysts. CuFe-NaY displays the best mineralization rate for PY oxidation while MnFe-NaY shows the highest activity for Tar degradation. This work may provide further insight into the design of Fenton-type bimetallic catalysts with improved catalytic properties for environmental remediation.